Study on the Application of Celecoxib in Preemptive Analgesia for Orthopedic Surgery - Bai, Guoyang; Sun, Xiaobo; Qin, Kai; Wang, Hongze; Dou, Qunli (Journal of Contemporary Medical Practice, 2025)
Continuous stimulation due to tissue injury after orthopedic surgery can lead to peripheral nerve and central nervous system sensitization, which makes patients more sensitive to pain. Preemptive analgesia refers to the method of analgesia before the spinal cord produces pain sensitization. By inhibiting the conduction of peripheral injury to the central nervous system, the central nervous system sensitization is reduced, so as to achieve the purpose of reducing postoperative pain. Good pain management can enable patients to get out of bed as soon as possible, accelerate postoperative recovery, and reduce hospitalization time and medical-related costs. In recent years, non-steroidal anti-inflammatory analgesics play an important role in preemptive analgesia. This paper mainly studies the application of celecoxib in preemptive analgesia in orthopedic surgery.